Development of High Order Thinking Skills (HOTS) Test Instruments on Thermochemistry Topics - Dwi Wida Novatania; Agus Kamaludin (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This research aims to develop Higher Order Thinking Skill (HOTS)-based test instruments on thermochemistry in the form of a valid and reliable multiple-choice question. This research applied Research and Development (R&D) design by using the development model of Borg & Gall. The respondents of this research were 55 high school students which came from nine different schools. The research objects were multiple-choice HOTS questions numbering 20 questions. The research data was obtained by validating the thermochemistry HOTS questions by material and media expert lecturers. High school chemistry teacher as a reviewer who assesses the questions and tested on students. The results showed that the product quality assessment by material expert 92.00%; product quality assessment by media expert 92.00%; and quality assessment by reviewers (high school chemistry teachers) 94.89 % in the Very Good category. The trial result data from the students were processed by using IBM SPSS Statistics 24 and it showed that nine questions were valid but not reliable.